Liver fibrosis progression in a cohort of young HIV and HIV/ HBV co-infected patients: A longitudinal study using non-invasive APRI and Fib-4 scores - Iacob, Diana Gabriela; Luminos, Monica; Benea, Otilia Elisabeta; Tudor, Ana-Maria; Olariu, Cristina Mihaela; Iacob, Simona Alexandra; Ruta, Simona (Frontiers in Medicine, 2022)
Background. The risk of liver fibrosis increases over time in HIV and HIV-HBV individuals even under antiretroviral treatment (ART), warranting a rigorous and periodic monitorization. Given the lower availability of transient elastography, we aimed to assess the longitudinal variation of two non-invasive liver fibrosis scores, APRI and Fib-4, in cases with HIV monoinfection, HIV-HBV co-infection and individuals with HBsAg-seroclearance Methods. We performed an observational retrospective study between 2013-2019 on 212 HIV patients including 111 individuals with HIV monoinfection, 62 individuals with HIV-HBV co-infection and positive HBsAg and 39 cases with HIV-HBV infection and HBsAg-loss. The groups were followed at 36, 48 and 60 months. Liver fibrosis was indicated by an APRI>0.5 or Fib-4≥1.45 score and advanced fibrosis by an APRI score >1.5 or Fib-4 >3.25. Logistic regression with generalized estimating equations (GEE) was used to assess the predictors for the presence of liver fibrosis over time. Results. During a median follow-up of 58.5 months the prevalence of liver fibrosis in all patients increased with 0.5% reaching 11.3% using an APRI score and with 0.9% reaching 10.8% using the Fib-4 score. At the visit corresponding to 60 months the prevalence of liver fibrosis was higher in all HIV-HBV patients compared with individuals with HIV monoinfection, namely: 16.1% on APRI and 12.9% on the Fib-4 score in HIV-HBV/HBsAg-positive individuals, 12.8% on both APRI and Fib-4 scores in HIV-HBV/HBsAg-negative individuals versus 8.1% and 9% respectively in HIV monoinfection. The presence of liver fibrosis over the study period was independently associated with plasma HIV RNA, CD4+T cell counts, HIV-HBV co-infection (for APRI>0.5) and ART non-adherence (for Fib-4>1.45). At the final visit, non-adherence to ART and CD4+T cell counts remained associated with liver fibrosis. Conclusions. The study found a slow progression of APRI and Fib-4 scores over time in young PLWH with extensive ART. Liver fibrosis scores continued to increase in patients with HIV monoinfection yet remained lower than in HIV-HBV patients irrespective on the presence of HBsAg. The periodic follow-up using non-invasive scores on the long-term could help improve the surveillance in low-income settings and high scores should be followed by additional diagnostic methods.